Sources of Light: What they can Reveal - Garg, Rachna (SCHOOL SCIENCE, 2015)
Human curiosity resulted in the invention of telescope and microscope enabling human beings to view far off objects, as well as very tiny objects, using visible light. With the discovery of electromagnetic spectrum, ways to produce and detect light beyond visible range were invented. The techniques were developed to explore using non-visible light, which resulted in rapidly expanding human knowledge about nature during last century.